Małżeństwo osób tej samej płci – sprawa Obergefell v. Hodges i inni - Wróbel, Agata Jagna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The purpose of this article is to examine, how the legal situation of persons living in homosexual relationships is regulated in the United States, Europe and Poland. This research is conducted with the use of comparative, legal dogmatic and descriptive methods. The key assumption is to state that despite lack of universal standards in the issue of recognition of same-sex couples, the institutionalization of the status of homosexual relationships is a dynamic and irreversible phenomenon. It should be noted that countries are aiming to regulate this matter, taking into account the tradition prevailing in a particular society, as well as the current public sentiment and the degree of citizens’ tolerance and sensitivity. At the same time this publication is an invitation to a discussion on the need to introduce appropriate legal solutions, regulating the situation of persons living in a homosexual relationships in Poland.
Keywords: rights of homosexuals; right to marriage; homosexuality; civil partnership; marriage; fundamental rights